Peran Akuntansi Perilaku Dalam Meningkatkan Efektivitas Pengambilan Keputusan Keuangan - Iwin Arnova; Bresman Marpaung (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The increasingly dynamic business environment requires financial decision-making processes that are not only based on accounting information but also consider the behavioral aspects of individuals involved in such processes. Behavioral accounting has emerged as a field of study that examines the relationship between accounting systems and human behavior within organizations. The present study investigates the contribution of behavioral accounting to more effectiveness financial decision-making. This study adopted a literature riview approach by reviewing relevant journal articles, books, and previous studies on behavioral accounting and financial decision making. The analysis was conducted through the identification, evaluation, and synthesis of various research findings to obtain a comprehensive understanding of how behavioral factors influence the quality of financial decisions. The results indicate that factors such as perception, motivation, experience, cognitive bias, organizational culture, and the level of understanding of accounting information significantly affect the effectiveness of financial decision-making. The application of behavioral accounting principles can assist organizations in understanding decision-makers’ behavior, thereby reducing judgment errors and improving decision quality. This study concludes that behavioral accounting plays a strategic role in supporting more rational, objective, and effective financial decision-making processes. Therefore, organizations should integrate behavioral aspects into accounting systems and managerial practices to enhance decision-making performance